Value of Noninvasive Electrophysiological Examination in Choice of Management of Children with Sinus Node Dysfunction - N.V. Nagornaya; Ye.V. Pshenichnaya; S.A. Parshin; Ye.S. Akobirov; A.V. Dubovaya; A.A. Burka (Zaslavsky O.Yu., 2012)
In the article there are presented the data about noninvasive electrophysiological examination and its application in pediatrics. The clinical case of observation of 15-year-old child who went in for sports for a long time, with sick sinus syndrome supposed in the beginning of diagnostic search, is resulted. The difficulties of differential diagnosis of this syndrome and vegetative dysfunction of sinus node are presented. The role of transesophageal pacing in making a diagnosis and solution of a question about necessity of artificial pacemaker implantation is shown.